2021
DOI: 10.3389/fcimb.2021.790422
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Composition of Intestinal DNA Virome in Patients With COVID-19

Abstract: Patients with Coronavirus Disease 2019 (COVID-19), due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection mainly present with respiratory issues and related symptoms, in addition to significantly affected digestive system, especially the intestinal tract. While several studies have shown changes in the intestinal flora of patients with COVID-19, not much information is available on the gut virome of such patients. In this study, we used the viromescan software on the latest gut virome da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
4
14
1
Order By: Relevance
“…1 Furthermore, increase of viral loads was influenced by the administration of specific antibiotics The observations reported in Ref. 1 are in line with additional ones reported more recently, like evidence that gut virome is affected by the SARS-CoV-2 infection and may play an important role in the disease progression of coronavirus disease 2019 (COVID-19), 2 the presence of SARS-CoV-2 nucleoprotein (N) in intestinal epithelial cells of approximately 35% of patients with COVID-19 even several weeks or months after initial diagnosis, 3 the high rate of positive polymerase chain reaction (PCR) findings in more than one type of clinical specimen collected up to 43 days after COVID-19 patients had presented the first symptom. 4 To investigate these observations in more detail, we designed and carried out three different experiments, which make use of electron microscopy (EM), mass spectrometry and next-generation sequencing (NGS).…”
Section: Introductionsupporting
confidence: 76%
“…1 Furthermore, increase of viral loads was influenced by the administration of specific antibiotics The observations reported in Ref. 1 are in line with additional ones reported more recently, like evidence that gut virome is affected by the SARS-CoV-2 infection and may play an important role in the disease progression of coronavirus disease 2019 (COVID-19), 2 the presence of SARS-CoV-2 nucleoprotein (N) in intestinal epithelial cells of approximately 35% of patients with COVID-19 even several weeks or months after initial diagnosis, 3 the high rate of positive polymerase chain reaction (PCR) findings in more than one type of clinical specimen collected up to 43 days after COVID-19 patients had presented the first symptom. 4 To investigate these observations in more detail, we designed and carried out three different experiments, which make use of electron microscopy (EM), mass spectrometry and next-generation sequencing (NGS).…”
Section: Introductionsupporting
confidence: 76%
“…In a recent study involving COVID‐19 patients, Myoviridae, Siphoviridae, Microviridae, Podoviridae , and crass‐like phages were detected in the virome of fecal DNA of patients. 23 The results from the study correlate with our findings. In addition, the study reported that the virome composition in the gut changed significantly in the COVID‐19 patients when compared with healthy controls and the significant changes might be related to the changes in the bacteriome composition.…”
Section: Resultssupporting
confidence: 89%
“…The phage abundance drastically reduces from the severe cases to the nonsevere cases. In a recent study involving COVID‐19 patients, Myoviridae, Siphoviridae, Microviridae, Podoviridae , and crass‐like phages were detected in the virome of fecal DNA of patients 23 . The results from the study correlate with our findings.…”
Section: Resultssupporting
confidence: 89%
“…Upon viral clearance, prior hyperinflammatory state and microbiome imbalance may damage gastrointestinal integrity and function [47]. Current findings have emphasized changes in the gut microbiota in patients following COVID-19 infection [48][49][50].…”
Section: Symptoms Of Long Covidmentioning
confidence: 99%
“…SARS-CoV-2 RNA can be detected from fecal samples during acute stage, indicating gastrointestinal (GI) involvement in COVID-19 pathology [46,76]. Recent studies reveal that gut microbiome diversity and composition are changed post COVID-19 infection [48][49][50]. Increase in viral-induced cytokines may compromise intestinal integrity, facilitating the entry of bacteria and metabolites into circulation.…”
Section: Gut Microbiotamentioning
confidence: 99%